Teleconnection between the North Indian Ocean high swell events and meteorological conditions over the Southern Indian Ocean. Issue 10 (13th October 2016) - Remya, P. G.; Vishnu, S.; Praveen Kumar, B.; Balakrishnan Nair, T. M.; Rohith, B.
Abstract: The link between North Indian Ocean (NIO) high swell events and the meteorological conditions over the Southern Indian Ocean (SIO) is explored in this article, using a combination of in situ measurements and model simulations for the year 2005. High waves, without any sign in the local winds, sometimes cause severe flooding events along the south‐west coast of India, locally known as the Kallakkadal events and cause major societal problems along the coasts. In situ observations report 10 high swell events in NIO during 2005. Our study confirms that these events are caused by the swells propagating from south of 30°S. In all cases, 3–5 days prior to the high swell events in NIO, we observed a severe low pressure system, called the Cut‐Off Low (COL) in the Southern Ocean. These COLs are quasistationary in nature, providing strong (∼25 ms −1 ) and long duration (∼3 days) surface winds over a large fetch; essential conditions for the generation of long‐period swells. The intense equator ward winds associated with COLs in the SIO trigger the generation of high waves, which propagate to NIO as swells. Furthermore, these swells cause high wave activity and sometimes Kallakkadal events along the NIO coastal regions, depending on the local topography, angle of incidence, and tidal conditions. Our study shows that such natural hazards along the NIO coasts can be forecasted at least 2 days in advance if the meteorological conditions of the SIO are properly monitored. Key Points: Kallakkadal flooding events along Indian coastline Southern Ocean swells Cut‐off Low and blocking patterns in the Southern Ocean